(untitled) (Szociológiai Szemle, 2024)
On the basis of a secondary analysis of the 25-year-series of longitudinal data on American households from the Panel Study of Income Dynamics (University of Michigan, Ann Arbor, USA), the authors estimate the influence of expectations and attitudes (concerning the future, the plannning of future activities, the control of one’s life-course, etc.) on economic outcomes. They find that people who expect to be economically successful will generally be so. The findings of previous research on this topic have been controversial and their evaluations anything but unanimous. The authors conclude that expectation-attitudes are instructive in determining people’s economic positions. Contextual factors such as family milieu and the nature of the spouse’s attitudes also play a certain role. Discussing the socio-political implications of their findings, the authors emphasize the effects of the symbolic environment on economic progress in society.